Drgania Belek Składanych z Nieliniowymi Efektami Luzów w Złączach - Nowacki, W.K.; Woroszył, S. (Engineering Transactions, 1963)
The problem under consideration is that of forced vibration taking into consideration the non- linear effects due to the clearances appearing in the joints. This problem is solved by the Rayleigh method, the vibration mode being determined on the grounds of the linear and nonlinear theory. This problem leads to a differential equation of motion which is linear with variable coefficients. Equation is given for the two cases under consideration that is with linearly and nonlinearly determined vibration mode. In the examples is shown the influence of the clearances on the dynamic coefficient of the beam.